A Li2S‐Based Sacrificial Layer for Stable Operation of Lithium‐Sulfur Batteries. Issue 11 (10th October 2018) - Ren, Y. X.; Zhao, T. S.; Liu, M.; Jiang, H. R.; Xiong, C.
Abstract: The polysulfide shuttle effect forms a formidable barrier for lithium‐sulfur (Li−S) battery technology, as it results in serious side reactions on the anode surface and shortens the battery's cyclability. In this work, we propose a facile yet effective preparation of the Li2 S‐based sacrificial layer (LSL) as the separator to retard polysulfide crossover. On one hand, before polysulfides (PS) reach the anode surface and react with Li metal, low‐order Li2 S prefilled inside the porous separator can chemically interact with PS and sterically physically block PS diffusion. On the other hand, the loss of Li2 S in LSL can be replenished by the chemical disproportion of polysulfides, rendering the LSL with excellent endurance over cycling. With the optimized LSL, the Li/polysulfide battery achieves a stabilized discharge capacity at 25 °C (>950 mAh g −1 for 300 cycles, 0.5 C) and demonstrates an excellent thermal stability even at 55 °C (>870 mAh g −1 for 150 cycles, 1 C). The strategy is further generalized to other sulfur based batteries ( i. e . Na−S battery), offering new opportunities to improve high‐energy sulfur‐based energy storage technologies. Abstract : We propose a facile preparation of the Li2 S‐based sacrificial layer (LSL) as the separator to retard polysulfide shuttles in lithium‐sulfur batteries. Before polysulfides (PS) reach the anode surface and react with Li metal, low‐order Li2 S prefilled inside the porous separator can chemically interact with PS and physically block PS diffusion. Also, the loss of Li2 S in LSL can be replenished by the chemical disproportion of polysulfides.